Twenty Years of Job Quality in OECD Countries: More Good News? - Andrew E. Clark; Michal Kozák (Institute of Labor Economics (IZA), 2023)
The distribution of job quality across workers and the change in job quality over time can be measured by job-domain indices or single-index job-satisfaction. This paper takes both approaches to establish the evolution of job quality over a period from the mid-1990s to the mid-2010s in 13 OECD countries, using data from the three latest ISSP Work Orientation modules. The rise in job satisfaction from 1997 to 2005 has continued through 2015, despite the 2008 Great Recession. This improvement is also found in most of the job-outcome domains, despite some evidence of work intensification. Job security was the most-important job aspect every year, and the percentage of workers with secure jobs rose over time. There has been a small rise in the dispersion of job satisfaction, but the good news regarding better job quality over a 20-year period does not seem to be dampened by large changes in its inequality.
Keywords: J28; J3; J81; 330; job quality; job satisfaction; ISSP